A descriptive Analysis of Anglicisms used in Ecuadorian Magazines. - Calva Abad, Ana María (2011)
The theme of this current research is A Descriptive Analysis ofAnglicisms in Ecuadorian Magazines, which pretends to analyze theuse of anglicisms in Spanish written language in Ecuador.This study was based on three variables : cultural magazines,scholarly magazines, and general interest magazine. It was carried outin Quito Ecuador.The methods used in this research were Qualitative andQuantitative.Once the variables were selected, it was mandatory to readthrough them to find the anglicisms. Then, all the words selected hadto be verified in a dictionary to know whether they were anglicisms ornot. The dictionaries used to verify the anglicisms were Merriam-Webster, and Diccionario de la Real Academia de la Lengua (DRAE).Finally, I developed a linguistic and comparative analysis ofeach anglicism regarding morphological, syntactic and semanticaspects.As a result of this study, I could figure out that the language isconstantly changing around the world; so, new words appear, and theyare used as prowIper, but in fact, they have another origin, as in the caseof anglicisms.